2018
DOI: 10.1051/matecconf/201819203011
|View full text |Cite
|
Sign up to set email alerts
|

Modified photoperiods and light intensities for grow-out production of nile tilapia (O. niloticus) under indoor tank culture system

Abstract: Abstract. The study aimed to evaluate the effect of modified photoperiods and light intensities on grow-out production of tilapia under indoor tank culture system; specifically on water quality and on growth performance of tilapia. The study was conducted inside the greenhouse and considered two factors: photoperiod (24L:0D, 20L:4D and 16L:8D); and light intensity (40 watts m -2 , 60 watts m -2 and 80 watts m -2 ); also, a control treatment was set-up outside the greenhouse to receive the normal environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…To optimize the growth of Oreochromis niloticus , it is recommended to use continuous lighting with a light intensity of more than 400 lx with 4 weeks of acclimatization before fish cultivation (Mustapha et al, 2012). In large‐volume indoor tanks, when growing the same species, it was found that good growth can be obtained in high light at 27 300 lx (Cinense et al, 2018).…”
Section: Growthmentioning
confidence: 99%
“…To optimize the growth of Oreochromis niloticus , it is recommended to use continuous lighting with a light intensity of more than 400 lx with 4 weeks of acclimatization before fish cultivation (Mustapha et al, 2012). In large‐volume indoor tanks, when growing the same species, it was found that good growth can be obtained in high light at 27 300 lx (Cinense et al, 2018).…”
Section: Growthmentioning
confidence: 99%